A randomized double blind comparison of atosiban in patients with recurrent implantation failure undergoing IVF treatment - Chuan Ling Tang; Qi Yue Li; Feng Lian Chen; Chen Ting Cai; Yue Yan Dong; Yuan Yuan Wu; Jian Zhi Yang; Mei Zhao; Feng Li Chi; Ling Hong; Ai Ai; Miao Xin Chen; et al. (BMC, 2022)
Abstract Background Patients with recurrent implantation failure (RIF) may have more uterine contractions. Several observational studies suggested that atosiban administration around embryo transfer resulted in higher pregnancy rates in RIF patients. This study aimed to evaluate the effect of atosiban given before fresh embryo transfer on pregnancy outcomes of women with RIF. Methods A prospective, randomized, double-blind controlled clinical trial was performed in IVF center of Shanghai First Maternity and Infant Hospital. According to a computer-generated randomization list, 194 infertile women with RIF received fresh embryo transfer between July 2017 and December 2019 were randomly allocated into the atosiban (n = 97) and the placebo (n = 97) groups. Women in the treatment group received atosiban intravenously about 30 min before embryo transfer with a bolus dose of 6.75 mg over one minute. Those in the placebo group received only normal saline infusion for the same duration. Results There was no significant difference in the live birth rate between the atosiban and placebo groups (42.3% vs 35.1%, P = 0.302, RR = 1.206 (0.844-1.723)). No significant differences were found between the two groups in the positive pregnancy test, clinical pregnancy, ongoing pregnancy, miscarriage, multiple pregnancy, ectopic pregnancy and implantation rates. Similar results were found when stratified by the number of embryos previously transferred, number of previous failed embryo transfers, frequency of endometrial peristalsis on embryo transfer day (≥ 3 waves/min) or serum estradiol (E2) on the day of hCG above the median level. And, there was no correlation between the serum E2 level on the day of hCG and the frequency of endometrial peristalsis on embryo transfer day. The frequency of endometrial peristalsis on embryo transfer day, total FSH/HMG dosage and duration were the significant factors which independently predicted the likelihood of a live birth. Conclusions These results suggested that atosiban treatment before fresh embryo transfer might not improve the live birth rate in RIF patients. Trial registration The study had been approved by the Institutional Review Board of the hospital (2017 ethics No.43) and was registered under Clinicaltrials.gov with an identifier NCT02893722.